ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PRUDENCE AKUNTANSI - Chrysti Despiana Saragih; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This research aims to analyze the effect of corporate governance mechanisms on accounting prudence in manufacturing companies in Indonesia. The variables tested in this research were size of the board of commissioners, independence of the board of commissioners and types of auditors as independent variables and accounting prudence as the dependent variable. This study uses a sample consisting of 264 manufacturing companies listed on the Indonesia Stock Exchange in 2015 - 2017. Sampling was done using a purposive sampling method with certain criteria. The analysis technique used is multiple regression analysis.The results of the analysis of this research indicate that the independent variables namely size of board of commissioners have a negative effect on accounting prudence while independence of the board of commissioners and types of auditor have a positive effect on accounting prudence.